Study on equations of curves of the squeezing machines’ contact of rolls - Turgunov Komil; Abdullaev Akhror (E3S Web of Conferences, 2023)
This study deals with the issues of mathematical modeling of curves of contact of rolls of squeezing machines. The paper deals with the issues of mathematical modeling of curves of contact of rolls of squeezing machines. Equations are obtained the of curves contact of the rolls of the squeezing machine, in which the upper roll is mixed relative to the lower roll towards the movement of the processed material, the processed material is fed so that the line, which is a continuation of its front end, passes through the axis of rotation of the upper roll. It was been established that the contact curves of the rolls depend mainly on the deformation and geometric parameters of the processed material and both rolls, as well as the coefficients of friction between the contacting bodies.